Colonialidade e neoliberalismo na formulação de políticas públicas: o projeto político do agronegócio no Brasil (2019 - 2022) - Costa, Karolayni Baldoni (2024)
The contemporary sociopolitical and economic context has been characterized by a complex interplay of forces, among which coloniality and neoliberalism stand out. In the Brazilian context, this dynamic gains particular relevance within the agri-food agenda. After all, agribusiness (and, consequently, the agro-lobby) wields significant influence in the Brazilian political system. An example of this is the Parliamentary Front for Agriculture, popularly known as the "Bancada Ruralista" which is the most influential caucus in national politics. However, not all organizations within the sector present a unanimous position, marked by what Caio Pompeia (2020) refers to as "programmatic differentiation." This relationship becomes clearer when observing the 2022 presidential election between Jair Messias Bolsonaro and Luiz Inácio Lula da Silva, during which the expressions "good agro" and "bad agro" became popular. In this sense, the question proposed is "what is the influence of coloniality and neoliberalism on the construction of Brazilian public policies, particularly in the agribusiness agenda?". It is argued that the system of neoliberal ideas and values, in interaction with Brazilian social structures marked by agrarian (colonial) issues and coloniality, shapes the agenda-setting process, making the agribusiness agenda the only alternative for economic development. However, this agenda is constantly strained by political and discursive disputes, especially regarding land issues and the constraints imposed by the international order, particularly by financial markets and international trade. These disputes reflect the complexity of the relationship between neoliberalism, coloniality, and development in the Brazilian context, determining the agri-food agenda. Therefore, the general objective is to map the process of Brazilian agri-food agenda formation, examining the trajectory of the ideas that originated and supported the agendas, the actors responsible for the ideas, and how they influenced policy-making during the Bolsonaro government (2019-2022). Thus, the specific objectives are: (i) To deepen the theoretical discussion on coloniality in the agenda-setting process and its contribution to the study of International Relations in the contemporary world; (ii) To map the actors, their agendas, and the strategies used in the process of forming the Brazilian agri-food agenda; (iii) To identify and analyze the political and discursive disputes within this agri-food agenda and how they are intersected by coloniality; (iv) To reflect on the social consequences of this model. As for methods, it will be a qualitative study, as it will be operationalized using methods document analysis, literature review, and Discourse and Content Analysis. The primary sources will comprise documents from the main entities associated with agribusiness and guidance from the Ruralist Caucus (“Bancada Ruralista”).